Barriers to the maturity of student’s career planning as millennial generation - Nurlela Nurlela; Endang Surtiyoni (Program Studi bimbingan Konseling PPs UNM Makassar, 2020)
Research aims to examine obstacles found both internally and externally. Method of research using survey method. Research population is an alumnus of study and counseling Program of PGRI Palembang University. Samples were chosen using the Purposif method, which focused on alumni who have not worked after graduating from college. The data collection techniques used are the scale of confusion in choosing a career. The results showed that there were students ' barriers in planning careers with both internal and external factors, but the barriers were dominated by internal factors.